Hubungan Antara Dukungan Sosial Orang Tua DenganKepercayaan Diri Pada Remaja Awal - Wibawani, Noviana Asri; , Dr. Wiwien Dinar Pratisti, M.Si (2016)
Self-confidence in adolescents was being built, so that condition is low. In fact, the self-confidence that is required for teenagers to establish positive identity. And, one of the influential factors is parent's social support. The purpose of this research is to determine: (1) the relationship between social support parents with confidence in adolescents the early age in junior high school, (2) the role of parent's social support with self-confidence early teens, and (3) the level of self-confidence early adolescence and the level of parent's social support in early teens. This research uses quantitative methods. The subjects involved are secondary school student aged 12-15 years is about 220, and retrieval of data using purposive sampling technique. A data collection tools in this study using a scale social support parents and self-confidence scale. The result showing rxy = 0,590 p = 0,000 (p<0,01) which is there are very significant relationship between parent's social support with self-confidence in the early teens junior high school age. Showing also that the level of social support parents and self-confidence in the early teens X Junior High School is considered high. 84% to the level of parent's social support and set at 69,9% to the level of self2 confidence in the early teens in X Junior High School. Parent's social support has an important (34,81% of r2 = 0,3481) on self-confidence in early teens. This study indicates that the importance of parent's social support to self-confidence in the early teens.